2016
DOI: 10.3390/w8060265
|View full text |Cite
|
Sign up to set email alerts
|

Flume Experiments for Optimizing the Hydraulic Performance of a Deep-Water Wetland Utilizing Emergent Vegetation and Obstructions

Abstract: Constructed ponds and wetlands are widely used in urban areas for stormwater management, ecological conservation, and pollution treatment. The treatment efficiency of these systems is strongly related to the hydrodynamics and hydraulic residence time. In this study, we developed a physical model and used rhodamine-WT as a tracer to conduct flume experiments. An equivalent Reynolds number was assumed, and the flume was a 1/25-scale model. Emergent obstructions (EOs), submerged obstructions (SOs), and high-and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…This emphasizes that there are also other factors that are important to consider for obtaining high nutrient removal in created wetlands in agricultural catchments. These can be factors related to wetland design and biological composition [33][34][35][36][37][38], as well as concentrations and form of the nutrients in inflowing water or other factors related to catchment characteristics [6,23,27,32]. Further studies are needed to identify and evaluate the important factors affecting the nutrient removal efficiency of created wetlands in agricultural catchments.…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes that there are also other factors that are important to consider for obtaining high nutrient removal in created wetlands in agricultural catchments. These can be factors related to wetland design and biological composition [33][34][35][36][37][38], as well as concentrations and form of the nutrients in inflowing water or other factors related to catchment characteristics [6,23,27,32]. Further studies are needed to identify and evaluate the important factors affecting the nutrient removal efficiency of created wetlands in agricultural catchments.…”
Section: Discussionmentioning
confidence: 99%
“…In his research work, turbulence properties were investigated by applying a k-ε turbulence model. Xia and Nehal [17] and Shih et al [18] experimentally investigated the features of flow in an open channel with vegetation. They used various arrangements of vegetation and investigated hydraulic characteristics in open channel flows.…”
Section: Introductionmentioning
confidence: 99%
“…where t n is the mean residence time in [h], as shown in Equation (3), and t m is the nominal retention time in [h] calculated from the first moment of the tracer response curve [6]:…”
Section: Hydraulic Performancementioning
confidence: 99%
“…In addition, Shih et al [6] and Chang et al [14] suggested that the addition of emergent baffles could considerably alter the hydraulic efficiency in a deep-water wetland. Therefore, several baffles with different lengths, widths, and aspect ratios were modeled.…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 1 more Smart Citation